Moulana Hali’s Reformic Thought and Iqbab’s Poetry: Analytical Study - DR. SYEDA TAYYABA RUBAB (دریافت)
Moulana Altaf Hussain Hali was a legend literary person. He freed the Urdu ghazal from old themes and introduced it to the larger scope of the diverse segments of life. He was a reformer, who pioneered modern literary attitude in Urdu literature. His poetic vision guided him about the literary revolution in Urdu. He recalled the religious, political and cultural history of Muslims and compared it to present. He wanted to aware the Muslims of subcontinent. Being the companion of Sir Syed Hali was diplomatic but after all he felt the serious and miserable condition of Muslim community in subcontinent and raised his voice in his poetry. Allama Iqbal was inspired by Hali, especially by his masterpiece "masaddas Maddo Jazer Islam" and by some other poems. Religious consciousness has gathered Allama Iqbal and Hali on the same platform Remembrance of glorious part of Muslim Ummah, Islamic golden ages, the sorrow of forgetfulness of our great ancestors, customs and the present condition of Muslim decline were the same reasons which influenced Iqbal and Hali, both, to write such poetry. We can trace Hali’s inspiration in the poetry of Iqbal. This article is a comprehensive study of Hali’s impacts on Iqbal’s poetry.